(untitled) (Intent Research Scientific Journal, 2023)
In this article, opinions are expressed about the methodological basis of the use of human resources in the activities of small business entities. Also, information about the current activities of small business entities, the attention paid to the use of human resources, and the reforms implemented in the field of development are given.